Engagement with mental health screening on mobile devices: Results from an antenatal feasibility study - Doherty,K; Marcano,Belisario J; Cohn,M; Mastellos,N; Morrison,C; Car,J; Doherty,G (ACM, 2019)
Perinatal depression (PND) affects up to 15% of women within the United Kingdom and has a lasting impact on a woman’s quality of life, birth outcomes and her child’s development. Suicide is the leading cause of maternal mortality. However, it is estimated that at least 50% of PND cases go undiagnosed. This paper presents the results of the first feasibility study to examine the potential of mobile devices to engage women in antenatal mental health screening. Using a mobile application, 254 women attending 14 National Health Service midwifery clinics provided 2,280 momentary and retrospective reports of their wellbeing over a 9-month period. Women spoke positively of the experience, installing and engaging with this technology regardless of age, education, wellbeing, number of children, marital or employment status, or past diagnosis of depression. 39 women reported a risk of depression, self-harm or suicide; two-thirds of whom were not identified by screening in-clinic.